Effects of substrate materials and liner thickness on the adhesive strength of the novel thin spray-on liner. (February 2020) - Chen, Lianjun; Zhou, Zhi; Liu, Guoming; Cui, Xiangfei; Dong, Qizheng; Cao, Huaixuan
In order to comprehensively investigate the influence of the thickness of thin spray-on liners on their adhesive strength with different surrounding rock environments, pull-off tests were employed to measure the adhesive strength of thin spray-on liners of different thickness on the surface of various substrates (granite, sandstone, concrete, and coal), which were used to simulate different surrounding rock environments. The results indicated that the failure mode was mainly liner material–substrate adhesion failure when granite, sandstone, or concrete was used as the substrate, while substrate failure was observed to occur more frequently when coal was used as the substrate. The variation rules of the adhesive strength ( σ ) of thin spray-on liners, along with liner thickness ( t ), for different surrounding rock environments were obtained:σ 1 = 3 . 11 × t − 0 . 5 for granite, σ 2 = 2 . 77 × t − 0 . 5 for sandstone, σ 3 = 2 . 95 × t − 0 . 5 for concrete, andσ 4 − 1 = 0 . 02 x + 1 . 765 ( t < 4) andσ 4 − 2 = 3 . 33 × t − 0 . 5 ( t ≥4) for coal. Furthermore, analysis of the standard deviation of experimental adhesive-strength data suggested that the variation in adhesive strength decreased in the following sequence: coal > concrete > sandstone > granite. The achievements of the current study provide a theoretical basis for the on-site determination of thin spray-on liner thickness requirements, as well as the scientific and rational design of liner material structure.